2017
DOI: 10.1186/s13071-017-2289-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro evaluation of contact activity of fluralaner, spinosad, phoxim, propoxur, permethrin and deltamethrin against the northern fowl mite, Ornithonyssus sylviarum

Abstract: BackgroundNorthern fowl mites (Ornithonyssus sylviarum) are obligate hematophagous ectoparasites of both feral birds and poultry, particularly chicken layers and breeders. They complete their entire life-cycle on infested birds while feeding on blood. Infestations of O. sylviarum are difficult to control and resistance to some chemical classes of acaricides is a growing concern. The contact susceptibility of O. sylviarum to a new active ingredient, fluralaner, was evaluated, as well as other compounds represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Results from the studies described in this report show that fluralaner is active against poultry red mites, isolated from commercial operations, showing decreased susceptibility to the most commonly used acaricides. These findings are consistent with reports of fluralaner efficacy against Ornithonyssus sylviarum , the northern fowl mite, particularly prevalent in North and Latin America, at similar exposure rates as those to which D. gallinae is sensitive [ 34 ]. They also align with previous results showing that fluralaner has been shown to overcome resistance in fleas, ticks or sea lice against phenylpyrazoles, amidines, organophosphates, cyclodienes, macrocyclic lactones, phenylpyrazoles, benzophenyl ureas, pyrethroids and carbamates [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Results from the studies described in this report show that fluralaner is active against poultry red mites, isolated from commercial operations, showing decreased susceptibility to the most commonly used acaricides. These findings are consistent with reports of fluralaner efficacy against Ornithonyssus sylviarum , the northern fowl mite, particularly prevalent in North and Latin America, at similar exposure rates as those to which D. gallinae is sensitive [ 34 ]. They also align with previous results showing that fluralaner has been shown to overcome resistance in fleas, ticks or sea lice against phenylpyrazoles, amidines, organophosphates, cyclodienes, macrocyclic lactones, phenylpyrazoles, benzophenyl ureas, pyrethroids and carbamates [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…This could account for the early rise of resistant D. gallinae populations, which was firstly documented more than 20 years ago (Beugnet et al, 1997) and it has been repeatedly reported from mites collected in poultry farms (Nordenfors et al, 2001;Thomas et al, 2018). A similar trend was observed for O. sylviarum populations collected in the field in California (Mullens et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Fluralaner is an isoxazoline compound that is approved for the treatment of poultry red mite infestations by two drinking-water administrations with a 7-day interval and having egg and meat withholding times of 0 and 14 days, respectively [ 12 ]. In vitro studies have demonstrated that field isolates of the northern fowl mite ( Ornithonyssus sylviarum ) and the PRM that are highly sensitive to fluralaner are relatively insensitive to other compounds, including spinosad, phoxim, propoxur and deltamethrin [ 13 , 14 ]. The mite-killing activity of fluralaner is evident within 4 h of the first administration and is maintained for at least the next 14 days [ 15 ].…”
Section: Introductionmentioning
confidence: 99%